Visible light initiation preparation method of renewable plant oil-based self-repairing photocureable coating monomer
By using renewable plant oil-based self-healing UV-curable coating monomers, combined with Diels-Alder dynamic reversible bonds and nanocomposite reinforcement technology, the problems of high equipment cost, dependence on petrochemical resources and low self-healing efficiency of traditional UV-curable coatings are solved, achieving efficient visible light curing, self-healing and improved mechanical properties.
Patent Information
- Application Number
- CN202511245183.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-11-14
AI Technical Summary
Traditional UV-cured coatings rely on expensive UV light equipment, are harmful to human health and the environment, are heavily dependent on petrochemical resources, have low self-healing efficiency, and lack mechanical properties.
By using renewable plant oil-based self-healing photocurable coating monomers, and through the Diels-Alder dynamic reversible bond and visible light response system, combined with nanocomposite reinforcement technology and organic bismuth catalysts, a coating with self-healing properties, high mechanical strength, and transparency was prepared.
It achieves efficient visible light curing, reduces equipment energy consumption, reduces dependence on petrochemical resources, improves self-healing efficiency and mechanical properties, and ensures high transparency.
Smart Images

Figure CN120944090A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a visible light initiation method for preparing a renewable plant oil-based self-healing photocurable coating monomer. Background Technology
[0002] In the coatings industry, traditional UV-cured coatings mostly rely on ultraviolet (UV) light curing. This not only requires specific UV light equipment, which is expensive, but also poses certain health risks to humans and the environment. Furthermore, existing coatings heavily utilize petrochemical resources, which contradicts the concept of sustainable development. Regarding self-healing properties, many self-healing coatings have low repair efficiency, failing to meet the durability and stability requirements of practical applications. In addition, the mechanical properties of coatings, such as hardness and scratch resistance, also need improvement.
[0003] Therefore, developing a high-efficiency, environmentally friendly photocurable coating with good self-healing and mechanical properties is of great practical significance. Summary of the Invention
[0004] To address the problems in existing technologies, this invention provides a visible light initiation method for preparing renewable vegetable oil-based self-healing photocurable coating monomers, thereby solving the aforementioned issues of traditional photocurable coatings. The photocurable coating monomers prepared by this method should possess high-efficiency visible light curing performance, good self-healing ability, excellent mechanical properties, and high visible light transmittance, while reducing dependence on petrochemical resources and meeting environmental protection requirements.
[0005] The technical solution adopted by this invention to solve its technical problem is: a visible light initiation preparation method for a renewable plant oil-based self-healing photocurable coating monomer, comprising the following steps: Step S1: Synthesis of vegetable oil-based prepolymer: Under nitrogen protection, epoxidized vegetable oil and a diacid anhydride containing a Diels-Alder dynamic reversible bond are mixed at a mass ratio of 2:1-3:1 and reacted at 40-60℃ for 2-4 hours to generate a vegetable oil-based prepolymer; the epoxidized vegetable oil is selected from at least one of epoxidized soybean oil and epoxidized castor oil, and the diacid anhydride is furan maleic anhydride; the purity of furan maleic anhydride is ≥98%, the furan ring substitution position is 2, and the anhydride group is connected to the furan ring through a methylene group; Step S2: Photosensitive functionalization modification: Add a visible light responsive monomer containing acrylate groups and a catalyst to the plant oil-based prepolymer obtained in step S1, and simultaneously add 0.1%-0.5% of 4A molecular sieve by mass of the total reaction system. React at 60-80℃ for 3-5 hours to obtain a photosensitive plant oil-based monomer; the visible light responsive monomer is an acrylate derivative, and the catalyst is an organobismuth compound; Step S3: Nanocomposite reinforcement: The photosensitive plant oil-based monomer and the surface-modified nano silica are mixed at a mass ratio of 6-10:1, ultrasonically dispersed for 20-40 minutes, and then polymerized in situ at 60-80℃ to form a nanocomposite resin. Step S4: Self-healing function integration: Add 0.5%-2% by mass of dynamic crosslinking agent to the nanocomposite resin. The dynamic crosslinking agent is a tetrafunctional compound containing furan / maleimide groups. Stir and mix evenly at room temperature to obtain the final photocurable coating monomer.
[0006] As a further technical solution, in step S1, the flow rate of nitrogen protection is 0.5-1 L / min.
[0007] As a further technical solution, the general structural formula of the visible light responsive monomer is: RO-(CH2) n −COO-C6H4−X, where R is acryloyloxy or methacryloyloxy, n=2-4, and X is a coumarin or thioxanone group.
[0008] As a further technical solution, in step S2, the amount of organic bismuth catalyst used is 0.01%-0.03% of the total mass of the reaction system, and the organic bismuth catalyst is at least one of bismuth isooctanoate, bismuth neodecanoate, or bismuth laurylate.
[0009] As a further technical solution, in step S3, the surface modification method for nano-silica includes: (1) Pretreatment: Add 10-50nm nano-silica to a 5%-6% hydrochloric acid solution and stir at 50-60℃ for 1-2 hours. Then wash with deionized water by centrifugation and vacuum dry at 80-100℃ for 4-6 hours to remove surface impurities and activate hydroxyl groups. (2) Preparation of modification solution: 3-mercaptopropyltrimethoxysilane and graphene quantum dots are mixed at a mass ratio of 14-20:1 and added to anhydrous ethanol. The amount of 3-mercaptopropyltrimethoxysilane is 5%-8% of the mass of nano-silica, and the mass ratio of anhydrous ethanol to nano-silica is 5-8:1. After stirring evenly, the mixture is ultrasonically dispersed for 15-20 minutes to obtain the modification solution. (3) Grafting reaction: The nano-silica pretreated in step (1) is added to the modification solution in step (2), heated to 60°C under nitrogen protection, and stirred for 4 hours. During this period, ultrasonic dispersion is performed for 5 minutes every 30 minutes to promote uniform grafting. (4) Post-treatment: After the reaction is completed, the mixture is centrifuged at 8000-10000r / min for 10-15 minutes, the precipitate is collected, and washed with anhydrous ethanol 3-4 times to remove unreacted modifiers. Finally, it is vacuum dried at 60-80℃ for 6-8 hours to obtain surface-modified nano silica.
[0010] As a further technical solution, in step S3, the in-situ polymerization time is 1-2 hours.
[0011] As a further technical solution, in step S4, the method for synthesizing the dynamic crosslinking agent is as follows: maleimide and furanol are mixed in a molar ratio of 1:4, and formic acid of 1%-2% of the total mass of the reaction system is added as a catalyst. The reaction is carried out under acidic conditions of pH 4-5 at 60-70°C for 6 hours. After recrystallization with ethyl acetate, the agent is dried under vacuum at 40-50°C for 8 hours to obtain the tetrafunctional dynamic crosslinking agent.
[0012] As a further technical solution, the curing conditions of the photocurable coating monomer are as follows: using a visible light source with a wavelength of 400-450nm, a light intensity of 50-100mW / cm2, and a curing time of 10-30 seconds.
[0013] As a further technical solution, the photocurable coating monomer is suitable for 3D printing materials, electronic device encapsulation coatings, or metal corrosion protection.
[0014] The beneficial effects of this invention are as follows: Bio-based and self-healing synergistic design: Using renewable vegetable oils as raw materials reduces dependence on petrochemical resources. The introduced dynamic Diels-Alder bonds endow the coating with self-healing capabilities. When the coating is damaged, under appropriate conditions, the broken Diels-Alder bonds can reconnect, achieving self-repair and extending the coating's service life.
[0015] Highly efficient visible light initiation system: Utilizing coumarin / thioxanthone derivatives as photoinitiators, this system overcomes the limitations of traditional UV curing. Curing with visible light reduces equipment energy consumption, improves operational safety, and avoids the harmful effects of UV light on humans and the environment.
[0016] Nanocomposite reinforcement technology: Surface-modified 3-mercaptopropyltrimethoxysilane forms covalent bonds with nano-silica, while the thiol group at the other end can chemically react with the acrylate groups in the photosensitive vegetable oil-based monomer, enabling the nanoparticles to form a stable chemical bond with the resin matrix, constructing a three-dimensional network structure that significantly improves the pencil hardness and scratch resistance of the coating. The modifier molecular chain reduces the surface energy of the nano-silica, preventing particle aggregation and ensuring uniform dispersion within the monomer, reducing the decrease in light transmittance caused by aggregation, and ensuring that the visible light transmittance of the cured coating is ≥85%. The modified nano-silica acts as a physical crosslinking point, synergistically working with dynamic Diels-Alder bonds. When the coating is damaged, it can temporarily maintain structural stability through interparticle interactions without hindering the recombination of reversible bonds, thus improving self-healing efficiency.
[0017] Low-temperature environmentally friendly process: Organic bismuth catalysts replace traditional tin catalysts, reducing the reaction temperature by 20%, reducing energy consumption, lowering production costs, meeting the requirements of green chemistry, and benefiting environmental protection. Attached Figure Description
[0018] Figure 1 This is a flowchart of a visible light-initiated preparation method for a renewable plant oil-based self-healing photocurable coating monomer. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] This invention provides a visible light initiation method for preparing a renewable plant oil-based self-healing photocurable coating monomer, comprising the following steps: Step S1: Synthesis of vegetable oil-based prepolymer Under nitrogen protection, epoxidized vegetable oil and diacid anhydride containing Diels-Alder dynamic reversible bonds are mixed at a mass ratio of 2:1-3:1 and reacted at 40-60℃ for 2-4 hours to generate vegetable oil-based prepolymer.
[0021] In this invention, the epoxidized vegetable oil is selected from at least one of epoxidized soybean oil and epoxidized castor oil, both of which are commercially available. The dicarboxylic anhydride is furan maleic anhydride with a purity ≥98%, the furan ring has a substitution position at position 2, and the anhydride group is connected to the furan ring via a methylene group.
[0022] In this invention, the nitrogen-protected flow rate is preferably 0.5-1 L / min, more preferably 0.8 L / min, to prevent oxidation of the reaction system and improve the structural stability of the prepolymer. The mass ratio of epoxidized vegetable oil to furan maleic anhydride is preferably 2.5:1, based on the reactivity of both, to ensure sufficient reaction between the anhydride groups and epoxy groups. The reaction temperature is preferably 50°C, and the reaction time is preferably 3 hours, which is more conducive to the stable introduction of dynamic reversible bonds.
[0023] Step S2: Photosensitive functionalization modification Add an acrylate-based visible light responsive monomer and an organic bismuth catalyst to the plant oil-based prepolymer obtained in step S1, and simultaneously add 0.1%-0.5% of 4A molecular sieve by mass of the total reaction system. React at 60-80℃ for 3-5 hours to obtain the photosensitized plant oil-based monomer.
[0024] In this invention, the visible light responsive monomer has the general structural formula RO-(CH2). n −COO-C6H4−X, wherein R is preferably acryloyloxy (more conducive to visible light response), n=2-4 (preferably 3), and X is a coumarin or thioxanone group.
[0025] The organic bismuth catalyst is selected from at least one of bismuth isooctanoate, bismuth neodecanoate, or bismuth laurate, with bismuth isooctanoate being preferred as it has higher catalytic efficiency. Its dosage is 0.01%-0.03% of the total mass of the reaction system, more preferably 0.02%, which can reduce residue while lowering the reaction temperature.
[0026] The optimal amount of 4A molecular sieve added is 0.3% of the total mass of the reaction system. This is used to adsorb trace amounts of moisture generated during the reaction and to avoid interference from hydroxyl groups on the photosensitive groups. The optimal reaction temperature is 70°C, and the optimal reaction time is 4 hours to ensure complete esterification of the prepolymer and the visible light-responsive monomer.
[0027] Step S3: Nanocomposite reinforcement Photosensitive plant oil-based monomers and surface-modified nano-silica are mixed at a mass ratio of 6-10:1, ultrasonically dispersed for 20-40 minutes, and then polymerized in situ at 60-80℃ for 1-2 hours to form a nanocomposite resin.
[0028] In this invention, the particle size of nano-silica is 10-50 nm, preferably 20-30 nm, and its surface modification method includes: (1) Pretreatment: Add nano-silica to a hydrochloric acid solution with a mass fraction of 5%-6%, stir at 50-60℃ for 1-2 hours, preferably 55℃ for 1.5 hours, centrifuge and wash until neutral, and then vacuum dry at 90℃ for 5 hours; (2) Preparation of modification solution: 3-mercaptopropyltrimethoxysilane and graphene quantum dots are mixed at a mass ratio of 14-20:1, preferably 17:1, and added to anhydrous ethanol and ultrasonically dispersed for 18 minutes; the mass ratio of anhydrous ethanol to nano silica is 6:1. (3) Grafting reaction: The pretreated nano-silica was added to the modification solution and stirred at 60°C for 4 hours under nitrogen protection (flow rate 0.4 L / min), and ultrasonically dispersed for 5 minutes every 30 minutes; (4) Post-treatment: Centrifuge at 9000 r / min for 12 minutes, wash three times with anhydrous ethanol, and vacuum dry at 70℃ for 7 hours to obtain surface-modified nano-silica.
[0029] The preferred mass ratio of photosensitive plant oil-based monomer to nano-silica is 8:1, the preferred ultrasonic dispersion time is 30 minutes for more uniform dispersion, the preferred in-situ polymerization temperature is 70℃, and the preferred time is 1.5 hours, which can form a stable nanocomposite structure.
[0030] Step S4: Self-repair function integration Add 0.5%-2% by mass of dynamic crosslinking agent to nanocomposite resin, stir and mix evenly at room temperature to obtain the final photocurable coating monomer.
[0031] The dynamic crosslinking agent is a tetrafunctional compound containing furan / maleimide groups. Its synthesis method is as follows: maleimide and furan-methanol are mixed in a molar ratio of 1:4, and 1.5% of formic acid (to adjust pH=4.5) of the total mass of the reaction system is added. The reaction is carried out at 65°C for 6 hours. After recrystallization from ethyl acetate, the mixture is dried under vacuum at 45°C for 8 hours.
[0032] The optimal amount of dynamic crosslinking agent added is 1.2% of the mass of the nanocomposite resin, which ensures self-healing properties while avoiding brittleness caused by excessive crosslinking. The optimal stirring time at room temperature is 30 minutes, with a rotation speed of 300 rpm, to ensure uniform dispersion.
[0033] The preparation method provided by this invention reduces petrochemical dependence by using renewable vegetable oil-based raw materials, introduces dynamic reversible bonds and visible light responsive groups, and combines nano-enhancement technology to enable the coating monomer to have efficient curing, self-healing and excellent mechanical properties, making it suitable for 3D printing materials, electronic device encapsulation coatings or metal corrosion protection.
[0034] The following are specific examples: Example 1 (1) Step S1: Under nitrogen protection (flow rate 0.5L / min), 100g of epoxidized soybean oil and 40g of furan maleic anhydride (mass ratio 2.5:1) were mixed and reacted at 50°C for 3 hours to obtain vegetable oil-based prepolymer. (2) Step S2: Add 50g of coumarin-type visible light responsive monomer (R=acryloyloxy, n=3), 0.03g of bismuth isooctanoate (0.02%) and 0.5g of 4A molecular sieve to the prepolymer, react at 70℃ for 4 hours to obtain photosensitized plant oil-based monomer; (3) Step S3: Mix 80g of photosensitive monomer with 10g of surface-modified nano silica (mass ratio 8:1), ultrasonically disperse for 30 minutes, and then polymerize in situ at 70℃ for 1.5 hours to form nanocomposite resin. (4) Step S4: Add 1.1g of dynamic crosslinking agent (1.2%) to the nanocomposite resin and stir at room temperature for 30 minutes to obtain the photocurable coating monomer.
[0035] Example 2 (1) Step S1: Under nitrogen protection (flow rate 0.8L / min), 120g of epoxy castor oil and 40g of furan maleic anhydride (mass ratio 3:1) were mixed and reacted at 60℃ for 2 hours to obtain a vegetable oil-based prepolymer. (2) Step S2: Add 60g of thioxanthone-type visible light responsive monomer (R=methacryloyloxy, n=2), 0.04g of bismuth neodecanoate (0.03%) and 0.6g of 4A molecular sieve to the prepolymer, react at 80℃ for 3 hours to obtain photosensitized vegetable oil-based monomer; (3) Step S3: Mix 90g of photosensitizing monomer with 10g of surface-modified nano silica (mass ratio 9:1), ultrasonically disperse for 40 minutes, and then polymerize in situ at 80℃ for 1 hour to form nanocomposite resin. (4) Step S4: Add 1.8g of dynamic crosslinking agent (2%) to the nanocomposite resin and stir at room temperature for 30 minutes to obtain the photocurable coating monomer.
[0036] Example 3 (1) Step S1: Under nitrogen protection (flow rate 1L / min), 100g of epoxidized soybean oil and 50g of furan maleic anhydride (mass ratio 2:1) were mixed and reacted at 40°C for 4 hours to obtain vegetable oil-based prepolymer. (2) Step S2: Add 40g of coumarin-type visible light responsive monomer (R=acryloyloxy, n=4), 0.02g of bismuth laurate (0.01%) and 0.3g of 4A molecular sieve to the prepolymer, react at 60℃ for 5 hours to obtain photosensitized plant oil-based monomer; (3) Step S3: Mix 60g of photosensitizing monomer with 10g of surface-modified nano silica (mass ratio 6:1), ultrasonically disperse for 20 minutes, and then polymerize in situ at 60℃ for 2 hours to form nanocomposite resin. (4) Step S4: Add 0.3g of dynamic crosslinking agent (0.5%) to the nanocomposite resin and stir at room temperature for 30 minutes to obtain the photocurable coating monomer.
[0037] Example 4 (1) Step S1: Under nitrogen protection (flow rate 0.7L / min), 110g of epoxidized soybean oil and 44g of furan maleic anhydride (mass ratio 2.5:1) were mixed and reacted at 55℃ for 3 hours to obtain vegetable oil-based prepolymer. (2) Step S2: Add 55g of thioxanthone-type visible light responsive monomer (R=acryloyloxy, n=3), 0.03g of bismuth isooctanoate (0.02%) and 0.4g of 4A molecular sieve to the prepolymer, react at 75℃ for 3.5 hours to obtain photosensitized vegetable oil-based monomer; (3) Step S3: Mix 88g of photosensitive monomer with 11g of surface-modified nano silica (mass ratio 8:1), ultrasonically disperse for 35 minutes, and then polymerize in situ at 75°C for 1.5 hours to form nanocomposite resin. (4) Step S4: Add 1.2g of dynamic crosslinking agent (1.2%) to the nanocomposite resin and stir at room temperature for 30 minutes to obtain the photocurable coating monomer.
[0038] Example 5 (1) Step S1: Under nitrogen protection (flow rate 0.6 L / min), 90 g of epoxy castor oil and 36 g of furan maleic anhydride (mass ratio 2.5:1) were mixed and reacted at 45 °C for 3.5 hours to obtain vegetable oil-based prepolymer; (2) Step S2: Add 45g of coumarin-type visible light responsive monomer (R=methacryloyloxy, n=3), 0.02g of bismuth neodecanoate (0.02%) and 0.4g of 4A molecular sieve to the prepolymer, react at 65℃ for 4.5 hours to obtain photosensitized plant oil-based monomer; (3) Step S3: Mix 72g of photosensitive monomer with 9g of surface-modified nano silica (mass ratio 8:1), ultrasonically disperse for 25 minutes, and then polymerize in situ at 65℃ for 1.5 hours to form nanocomposite resin. (4) Step S4: Add 0.9g of dynamic crosslinking agent (1%) to the nanocomposite resin and stir at room temperature for 30 minutes to obtain the photocurable coating monomer.
[0039] Comparative Example 1 The difference from Example 1 is that no dynamic crosslinking agent was added in step S4, while the remaining steps and parameters are the same.
[0040] Comparative Example 2 The difference from Example 1 is that unmodified nano-silica is used in step S3, while the other steps and parameters are the same.
[0041] test Self-repair performance test Method: Each example of the coating monomer was coated onto a tinplate (50 μm thick) and cured according to claim 8 (wavelength 420 nm, light intensity 80 mW / cm²). 2 (Time: 20 seconds); A cross-shaped scratch with a depth of 50 μm was made with a utility knife. After heating at 80℃ for 30 minutes, the change in scratch width was observed using an optical microscope, and the repair rate was calculated (repair rate = (initial width - repaired width) / initial width × 100%). The results are as follows: Table 1
[0042] As shown in Table 1, the repair rates of Examples 1-5 are all ≥89%. This is because the dynamic crosslinking agent works synergistically with the Diels-Alder bonds in the prepolymer, and the reversible bond recombination after heating achieves efficient repair.
[0043] Mechanical performance testing method: Pencil hardness: Tested according to GB / T6739-2006, using Mitsubishi pencils; Adhesion: Tested according to GB / T9286-1998 (cross-cut test), with a cross-cut spacing of 1mm. The results are as follows: Table 2
[0044] As can be seen from Table 2, the pencils of Examples 1-5 have a hardness ≥3H and an adhesion grade of 0 because the nano-silica has good compatibility with the resin matrix, forming a reinforcing network.
[0045] Visible light transmittance test Method: The coating monomer was coated onto quartz glass (100 μm thick). After curing, the transmittance in the 400-760 nm wavelength range was measured using a UV-Vis spectrophotometer (model UV-2600). The average value was taken, and the results are as follows: Table 3
[0046] As shown in Table 3, the transmittance of Examples 1-5 is ≥86% because the nano-silica is uniformly dispersed after surface modification and there is no obvious agglomeration. Comparative Example 1, due to insufficient cross-linking, has a loose molecular arrangement and a slightly lower transmittance.
[0047] In summary, this invention, through specific raw material ratios and processes, enables the coating monomers to outperform the comparative example in terms of self-healing properties, mechanical properties, and light transmittance. In particular, the use of dynamic crosslinking agents and organic bismuth catalysts is the key to performance improvement.
[0048] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A visible light initiation preparation method for a renewable plant oil-based self-healing photocurable coating monomer, characterized in that, Includes the following steps: Step S1: Synthesis of vegetable oil-based prepolymer: Under nitrogen protection, epoxidized vegetable oil and a diacid anhydride containing a Diels-Alder dynamic reversible bond are mixed at a mass ratio of 2:1-3:1 and reacted at 40-60℃ for 2-4 hours to generate a vegetable oil-based prepolymer; the epoxidized vegetable oil is selected from at least one of epoxidized soybean oil and epoxidized castor oil, and the diacid anhydride is furan maleic anhydride; the purity of furan maleic anhydride is ≥98%, the furan ring substitution position is 2, and the anhydride group is connected to the furan ring through a methylene group; Step S2: Photosensitive functionalization modification: Add a visible light responsive monomer containing acrylate groups and a catalyst to the plant oil-based prepolymer obtained in step S1, and simultaneously add 0.1%-0.5% of 4A molecular sieve by mass of the total reaction system. React at 60-80℃ for 3-5 hours to obtain a photosensitive plant oil-based monomer; the visible light responsive monomer is an acrylate derivative, and the catalyst is an organobismuth compound; Step S3: Nanocomposite reinforcement: The photosensitive plant oil-based monomer and the surface-modified nano silica are mixed at a mass ratio of 6-10:1, ultrasonically dispersed for 20-40 minutes, and then polymerized in situ at 60-80℃ to form a nanocomposite resin. Step S4: Self-healing function integration: Add 0.5%-2% by mass of dynamic crosslinking agent to the nanocomposite resin. The dynamic crosslinking agent is a tetrafunctional compound containing furan / maleimide groups. Stir and mix evenly at room temperature to obtain the final photocurable coating monomer.
2. The method according to claim 1, characterized in that, In step S1, the flow rate of nitrogen protection is 0.5-1 L / min.
3. The method according to claim 1, characterized in that, The general structural formula of the visible light responsive monomer is: RO-(CH2) n −COO-C6H4−X, where R is acryloyloxy or methacryloyloxy, n=2-4, and X is a coumarin or thioxanone group.
4. The method according to claim 1, characterized in that, In step S2, the amount of organic bismuth catalyst used is 0.01%-0.03% of the total mass of the reaction system, and the organic bismuth catalyst is at least one of bismuth isooctanoate, bismuth neodecanoate, or bismuth laurylate.
5. The method according to claim 1, characterized in that, In step S3, the surface modification method for nano-silica includes: (1) Pretreatment: Add 10-50nm nano-silica to a 5%-6% hydrochloric acid solution and stir at 50-60℃ for 1-2 hours. Then wash with deionized water by centrifugation and vacuum dry at 80-100℃ for 4-6 hours to remove surface impurities and activate hydroxyl groups. (2) Preparation of modification solution: 3-mercaptopropyltrimethoxysilane and graphene quantum dots are mixed at a mass ratio of 14-20:1 and added to anhydrous ethanol. The amount of 3-mercaptopropyltrimethoxysilane is 5%-8% of the mass of nano-silica, and the mass ratio of anhydrous ethanol to nano-silica is 5-8:
1. After stirring evenly, the mixture is ultrasonically dispersed for 15-20 minutes to obtain the modification solution. (3) Grafting reaction: The nano-silica pretreated in step (1) is added to the modification solution in step (2), heated to 60°C under nitrogen protection, and stirred for 4 hours. During this period, ultrasonic dispersion is performed for 5 minutes every 30 minutes to promote uniform grafting. (4) Post-treatment: After the reaction is completed, the mixture is centrifuged at 8000-10000r / min for 10-15 minutes, the precipitate is collected, and washed with anhydrous ethanol 3-4 times to remove unreacted modifiers. Finally, it is vacuum dried at 60-80℃ for 6-8 hours to obtain surface-modified nano silica.
6. The method according to claim 1, characterized in that, In step S3, the in-situ polymerization time is 1-2 hours.
7. The method according to claim 1, characterized in that, In step S4, the method for synthesizing the dynamic crosslinking agent is as follows: maleimide and furanol are mixed in a molar ratio of 1:4, and formic acid of 1%-2% of the total mass of the reaction system is added as a catalyst. The reaction is carried out under acidic conditions of pH 4-5 at 60-70°C for 6 hours. After recrystallization with ethyl acetate, the agent is dried under vacuum at 40-50°C for 8 hours to obtain the tetrafunctional dynamic crosslinking agent.
8. The method according to claim 1, characterized in that, The curing conditions for the photocurable coating monomer are as follows: using a visible light source with a wavelength of 400-450nm and a light intensity of 50-100mW / cm². 2 The curing time is 10-30 seconds.
9. The method according to claim 1, characterized in that, The photocurable coating monomer is suitable for 3D printing materials, electronic device encapsulation coatings, or metal corrosion protection.